Attitude towards public transport infrastructure use and maintenance in Nigeria (2013)
Infrastructure is indispensable to the socio-economic development of any nation. Transportation infrastructure is even more critical because the functioning of other infrastructures depend on it. However, the condition of some of the transport infrastructure particularly public transport infrastructure is appalling due to neglect, poor maintenance and the attitude of the citizens using them. For instance, refuse are dumped into drains, walkways converted to parking lots while road shoulders serve as platform for drying food stuffs, especially in rural communities. Roads are cut for water pipes, electricity and mobile phone cables without adequate repair. This aggravates the spate of deterioration of these facilities. The runways, rail tracks and jetties are not left due to long years of neglect. The paper calls for shared responsibility among the citizens, community and government in ensuring adequate maintenance of public transport infrastructure in Nigeria.